(untitled) (The Review of Diabetic Studies, 2025)
Introduction: Diabetic neuropathy is a prevalent complication of diabetes, potentially involving acoustic reflexes. Aim: To assess the acoustic reflex arc in diabetic individuals and investigate the impact of diabetes on ipsilateral and contralateral acoustic reflex thresholds in patients with normal hearing, in comparison to non-diabetic counterparts. Methods: A case-control study involving 120 participants, categorised into 30 with uncontrolled diabetes, 30 with controlled diabetes, and 60 healthy individuals aged 18-45 years. All participants underwent otoscopy, pure tone audiometry, tympanometry, and assessment of acoustic reflex thresholds (both ipsilateral and contralateral). Results: At a frequency of 500 Hz, the acoustic reflexes exhibited no statistically significant differences among the tested groups. At frequencies of 1000 Hz and 2000 Hz, substantial differences were observed between the uncontrolled diabetic group and the control group, but not between the controlled diabetic group and the control group. Conclusion: The acoustic reflex threshold elevates in uncontrolled diabetic adult patients, particularly at high frequencies, suggesting central neuropathy.